Regulation of Esports in the Context of the Employment in Indonesia - Pradana, Syafa’at Anugrah; Pikahulan, Rustam Magun; Alvian, Muh. Andri; Adriana, Sri (Amsir Law Journal, 2022)
This study aims to understand and analyze the legal arrangements of esports in terms of the point of view of labor law. The research method used is legal research with a normative juridical approach. The research results obtained are first, in terms of legal substance, second, in terms of legal structure, and third, in terms of legal culture. The author reflects that in the substance of the law, there has not been a single piece of legislation that contains explicitly and comprehensively regarding esports. Then in the aspect of esports dispute resolution, that is, the phrase “final and binding” on the award of the settlement of violations by Executive Board of Esports Indonesia is biased. In addition, in terms of legal culture, the existence of esports in Indonesia has risen in all walks of life, players who are legal subjects in esports are dominated by underage players. This study concludes that the government needs to form a law that explicitly regulates esports activities in Indonesia, in the form of: 1) The rights of esports athletes, especially minors; 2) The legal position of the Executive Board of Esports Indonesia statute in the laws and regulations in Indonesia; 3) Rights and obligations of esports athletes.